Agricultural productivity and nutrition: The role of women - Wijk, Mark T. van (International Livestock Research Institute, 2016)
It is often assumed that increasing agricultural productivity leads to a better diet. But in fact the relationship is more complex, and gender has an important role in mediating it. There are only a few harmonized datasets available, so the research team built its own tool and used it around the world in different systems. There was a sharp contrast between Africa and Asia. In East Africa, greater market orientation does not lead to better diets because money is spent in lots of ways other than nutrition. In Asia, women have much more control over agriculture and cash, which means that an increase in productivity does improve diets. In Africa, to improve diets it is better to work on crop diversification. Interview with Mark van Wijk (ILRI) for the book "A different kettle of fish? Gender integration in livestock and fish research". http://hdl.handle.net/10568/76684